Association between subjective degree of influence in class and thinness among adolescents in Japan - Ishikawa, Nanako; Koyama, Yuna; Doi, Satomi; Isumi, Aya; Fujiwara, Takeo (Frontiers in Pediatrics, 2023)
Social status in school, measured by subjective degree of influence in class (DOI), may influence thinness among adolescents. This study examined the association between subjective degree of influence in class and thinness among Japanese adolescents. Data were obtained from the Kochi Child Health Impact of Living Difficulty (K-CHILD) study in 2016, which is a population-based study targeting 5th, 8th and 11th grade adolescents living in Kochi Prefecture, Japan (N = 9,998). DOI was assessed by adolescents via questionnaire. Weight and height were given by caregivers for 5th grade adolescents, whilst they were self-reported for 8th and 11th grade adolescents. Collected data on weight and height were used to calculate body mass index z-scores of WHO standards. Adjusted covariates included grade, gender, number of friends, household income, location of school and depressive symptoms. Both high and low DOI were positively associated with thinness after adjustment for other individual covariates (high DOI, OR= 1.59, 95% CI 1.05-2.43; low DOI, OR= 2.04, 95% CI 1.36-3.06). Further stratification by gender revealed that low DOI was positively associated with thinness (OR= 2.14, 95% CI 1.34-3.44) among boys, but there was no association among girls. Both high and low DOI were associated with the risk of being thin in adolescents. Focusing on DOI for adolescents may be important to address thinness among adolescents. Further studies are needed to examine the causality between DOI and thinness in adolescents.